2015
DOI: 10.1111/tbed.12337
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Ratio for the Local Spread of African Swine Fever in Wild Boars in the Russian Federation

Abstract: African swine fever (ASF) has caused the swine industry of the Russian Federation substantial economic losses over the last 7 years, and the disease spread from there to a number of neighbouring countries. Wild boar has been involved in the spread of the disease both at local and at transboundary levels. Understanding ASF dynamics in wild boars is prerequisite to preventing the spread and to designing and applying effective surveillance and control plans. The reproductive ratio (R ) is an epidemiological indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 26 publications
7
73
0
2
Order By: Relevance
“…Recent publications have discussed the risk of ASFV introduction when importing pigs [10]. Illegal pork trade and the use of food waste in the animals feeding are recognized the most significant anthropogenic factors of the ASFV dissemination [20][21][22]. Moreover, a large number of private farms with their low bi-osafety level poses additional risks of the disease occurrence and dissemination Previously, Spanish researchers showed that ASFV could persist for several weeks or months in the frozen [23], freshly prepared or raw, as well as salted dried meat [24,25], which was in line with our findings When extrapolating our findings on natural and agricultural objects, it should be focused on the need to observe basic sanitary rules, given the fact that the virus can remain virulent for more than 2 weeks under favorable environment.…”
Section: Titers Of African Swine Fever Virus (Lg Haumentioning
confidence: 99%
“…Recent publications have discussed the risk of ASFV introduction when importing pigs [10]. Illegal pork trade and the use of food waste in the animals feeding are recognized the most significant anthropogenic factors of the ASFV dissemination [20][21][22]. Moreover, a large number of private farms with their low bi-osafety level poses additional risks of the disease occurrence and dissemination Previously, Spanish researchers showed that ASFV could persist for several weeks or months in the frozen [23], freshly prepared or raw, as well as salted dried meat [24,25], which was in line with our findings When extrapolating our findings on natural and agricultural objects, it should be focused on the need to observe basic sanitary rules, given the fact that the virus can remain virulent for more than 2 weeks under favorable environment.…”
Section: Titers Of African Swine Fever Virus (Lg Haumentioning
confidence: 99%
“…According to proposed estimates of the overall reproductive ratio of ASF in wild boar of Russian Federation (Iglesias et al 2015) the required level of wild boar density that would stop spread of ASF in wild boar would be between 0.1 and 0.2 animals per sqkm (see the density map in Fig. 3 in EFSA , 2015).…”
Section: %mentioning
confidence: 99%
“…Factors that may lead to spread of ASFV in the Russian Federation have been described in detail (Gulenkin et al, 2011;Sánchez-Vizcaíno et al, 2012FAO, 2013;Gogin et al, 2013;Oganesyan et al, 2013;EFSA, 2014;Korennoy et al, 2014;Iglesias et al, 2015). The involvement of different mechanisms leading to long-term circulation of ASFV is shown in Figure 6.…”
Section: Spatio-temporal Observations Wild Boar-domestic Pig Interfacementioning
confidence: 97%
“…According to estimates of the overall reproductive rate of ASF in wild boar of Russian Federation (Iglesias et al, 2015), the wild boar density required to stop spread of ASF in wild boar would be between 0.1 and 0.2 animals per square km (see the density map in Figure 19). Literally translated, the same transmission dynamics would require 80-90 % of the wild boar population in the affected Member States to be culled (see scenario 'massive short-term population destruction').…”
Section: 4mentioning
confidence: 99%